The Merger of Medical Universities in Iran: Challenges and Obstacles - Ali Mohammad Mosadeghrad; Reza Majdzadeh; Mohammad Arab; Amjad Mohamadi-Bolbanabad (Shahid Sadoughi University of Medical Sciences, 2019)
Background: Three big medical universities were merged in Iran in 2010, but they separated again after 2.5 years. The purpose of this study was to identify the most important challenges of this merger. Methods: This qualitative study was conducted using semi-structured interviews with 63 participants from April to September 2015. The data were analyzed via conventional content analysis method using MAXQDA10 software. Results: The merger of universities faced strategic, procedural, structural, contextual, and human resources' challenges. Factors such as the merger's vision, goals, and motives, the stakeholders' involvement, the merger announcement and time, interruption in service delivery, information systems, power balance, organizational structure, geographical distance, organizational culture, employees' reaction, and education influenced the failure of this merger. Conclusion: Merger and acquisition require a well-designed plan for the effective and efficient use of resources to achieve the desired outcomes. Therefore, policymakers should involve universities' managers and employees in decision-making process to achieve the best results.